Long-Term Hydrothermal Aging Behavior and Aging Mechanism of Glass Fibre Reinforced Polyamide 6 Composites. Issue 2 (1st February 2018) - Li, Ruiguang; Ye, Lin; Li, Guangxian
ABSTRACT: Long-term hydrothermal aging of polyamide 6 (PA6)/glass fibre (GF) composites was conducted and the effects of the GF on variations of structure and properties of the composites with aging time were investigated. It was found that the first stage of aging was a Fickian process and corresponded to the physical absorption of water until equilibrium, resulting in a slight change of reduced viscosity and chemical structure of the PA6. The water diffusing process was slowed down slightly by addition of the GF. The second stage of aging was the initiation process of hydrolytic degradation of PA6, resulting in a rapid decrease of reduced viscosity and an increase of end group content. In the final stage of aging, the relative weight gain ( W r ) dropped, the reduced viscosity decreased and the end groups increased slowly. The degradation rate and carbonyl index of PA6 increased with increasing GF content, and the increasing rate of end groups concentration of the composites was higher than that of pure PA6 during the aging process, indicating addition of GF accelerated the hydrolysis degradation and oxidative aging of PA6. In mechanical property tests, compared with unaged samples of the composites which underwent matrix rupture around the matrix-fiber interfacial layer, for aged samples several smooth fibres without coatings were pulled out and the interfacial debonding was the main failure mode, causing severe deterioration in mechanical properties. The hydrolytic degradation activation energy ( Ea ) was calculated through a method based on the Arrhenius model by considering both temperature and humidity as environment factors; with increasing GF content, Ea decreased, indicating that the addition of GF made PA6 easier to degrade.